Europäische Menschenrechtskonvention: EMRK-Kommentar - Frowein, Jochen Abr.; Peukert, Wolfgang (Engel, 1985)
Jochen Frowein/Wolfgang Peukert: Europäische Menschenrechtskonvention. EMRK-Kommentar. N. P. Engel Verlag, Kehl, Straßburg, Arlington 1985. 604 Seiten, 188 Mark
Literaturverz. S. 582 - 593
Keywords: Convention for the Protection of Human Rights and Fundamental Freedoms -- (1950 November 5); Kommentar; Convention for the Protection of Human Rights and Fundamental Freedoms (1950-11-04)